The influence of decentralized taxes and intergovernmental grants on local spending volatility. Issue 4 (3rd April 2017) - Sacchi, Agnese; Salotti, Simone
ABSTRACT: The influence of decentralized taxes and intergovernmental grants on local spending volatility. Regional Studies . This paper studies what affects the volatility of sub-central public spending in 20 Organisation for Economic Co-operation and Development (OECD) countries. The evidence based on data from 1972 to 2007 shows that the volatility of intergovernmental grants from upper levels is positively associated with the volatility of local expenditure. On the other hand, the volatility of local tax revenues – mainly that of property taxes – exerts the opposite effect. These findings suggest that making local governments rely more on grants than own tax revenues adversely affects their spending stability. Allowing them to levy autonomously taxes relying on responsive tax bases provides incentives to smooth their expenditure.